Light‐Controlled Growth Factors Release on Tetrapodal ZnO‐Incorporated 3D‐Printed Hydrogels for Developing Smart Wound Scaffold. (19th February 2021) - Siebert, Leonard; Luna‐Cerón, Eder; García‐Rivera, Luis Enrique; Oh, Junsung; Jang, JunHwee; Rosas‐Gómez, Diego A.; Pérez‐Gómez, Mitzi D.; Maschkowitz, Gregor; Fickenscher, Helmut; Oceguera‐Cuevas, Daniela; Holguín‐León, Carmen G.; Byambaa, Batzaya; et al.
Abstract: Advanced wound scaffolds that integrate active substances to treat chronic wounds have gained significant recent attention. While wound scaffolds and advanced functionalities have previously been incorporated into one medical device, the wirelessly triggered release of active substances has remained the focus of many research endeavors. To combine multiple functions including light‐triggered activation, antiseptic, angiogenic, and moisturizing properties, a 3D printed hydrogel patch encapsulating vascular endothelial growth factor (VEGF) decorated with photoactive and antibacterial tetrapodal zinc oxide (t‐ZnO) microparticles is developed. To achieve the smart release of VEGF, t‐ZnO is modified by chemical treatment and activated through ultraviolet/visible light exposure. This process would also make the surface rough and improve protein adhesion. The elastic modulus and degradation behavior of the composite hydrogels, which must match the wound healing process, are adjusted by changing t‐ZnO concentrations. The t‐ZnO‐laden composite hydrogels can be printed with any desired micropattern to potentially create a modular elution of various growth factors. The VEGF‐decorated t‐ZnO‐laden hydrogel patches show low cytotoxicity and improved angiogenic properties while maintaining antibacterial functions in vitro. In vivo tests show promising results for the printed wound patches, with less immunogenicity and enhanced wound healing. Abstract : To treat chronic wounds, a smart wound scaffold based on growth factors decorated tetrapodal zinc oxide (t‑ZnO)‐laden 3D printed hydrogel patches, which possess light‐triggered activation, anti‐bacterial, angiogenic, and tissue regeneration properties is reported. Through in vivo tests, the multi‐functional wound scaffolds show less immunogenicity and enhance wound healing, which make them interesting candidates for future smart wound dressing platforms.